Uncommon Metastasis of Laryngeal Cancer to Small Bowel Causing Intestinal Obstruction Treated by Laparoscopic Approach - Omar Bekdache; Lateefa Al Nuaimi; Haytham El Salhat; Vasudev Sharma; Ghodratollah Nowrasteh; Sadir J. Al Rawi (Case Reports in Surgery)
Metastatic laryngeal cancer to the small bowel is extremely rare. Management of small bowel obstruction used to constitute a relative contraindication for the use of laparoscopic modality. We are reporting a case of an elderly man known to have laryngeal cancer who presented with small bowel obstruction due to metastatic deposit to the small bowel. The condition was successfully treated by laparoscopic assisted approach. A review of the natural history of advanced laryngeal cancer, common and uncommon sites of metastasis, and the rare presentation as small bowel obstruction is illustrated in this review.